TRANSFORMATION AND RESPONSE OF ISLAMIC EDUCATION IN THE DISRUPTION ERA - Fajarudin, Akhmad Afnan (Tsaqofah : Jurnal Pendidikan Islam, 2022)
The fundamental problem of the world of education in Indonesia is the low quality of education. This is shown, with the still high inequality of the quality of education between regions. Indicators of educational development at the provincial level show two trends, namely in categories above national standards and below national standards. Indicators of the quality of education can be seen in participation figures, dropout numbers, class repeat numbers, teacher-student ratio, teacher-school eligibility level, and condition of school facilities and infrastructure. Islamic education in its existence as a component of nation building, especially in Indonesia, plays a very large role and this took place since long before the independence of the Indonesian nation. This can be seen in the practice of Islamic education organized by Muslims through traditional educational institutions such as taklim assemblies, study forums, surau and pesantren that thrive and exist until now.